Percutaneous transcatheter retrieval of intracardiac central venous catheter fragments in two infants using Amplatz Goose Neck snare - Tutar, Ercan; Aypar, Ebru; Atalay, Semra; Yavuz, Gülsan; Doğu, Figen (The Turkish Journal of Pediatrics, 2009)
Central venous catheter (CVC) fracture with embolization is a serious and rare complication, and few cases have been reported in children. Catheter fragments may cause cardiac perforation, arrythmias, pulmonary embolism, and sepsis. We report the successful retrieval of intracardiac CVC fragments by percutaneous transcatheter technique in two infants, aged 8 and 15 months. Double-lumen 7 French Hickman CVCs were accidentally fractured during their removal. Chest radiographs of the two patients revealed migrated intracardiac catheter fragments extending from the superior vena cava (SVC) to the right atrium and from the SVC to the right ventricle, respectively. The procedure was performed under ketamine anesthesia and fluoroscopic guidance using a percutaneous femoral vein approach. Nitinol Amplatz Goose Neck snares (10 mm in diameter) were used to successfully retrieve the catheter fragments without any complication. Percutaneous transcatheter retrieval of catheter fragments using Goose Neck snare is a safe and successful technique and can be chosen before resorting to surgery, which has potential risks related to general anesthesia, thoracotomy and cardiopulmonary bypass.